Subjective Quality Assessments in Virtual Environments - Tabesh, A.; Hussain, Farookh Khadeer; Chang, Elizabeth; Sianaki, Omid (IEEE Computer Society, 2010)
Being able to make objective Quality of Service (QoS) judgments or assessments is a challenging and crucial activity. The process of making these assessments is compounded when the environment in which the assessments have to be made are virtual; in the sense the interacting parties might not have necessarily metwith each other physically. In a broad sense Quality of Service assessments could be broadly categorized into two areas, namely objective assessments and subjective assessments. In this paper, we propose a suite of metrics to carry out subjective quality assessment in a virtual environment.